Transmission of caprine arthritis encephalitis virus between sheep - Carla Caroline Valença de Lima (Ciência Rural, 2018)
ABSTRACT: This study was conducted to evaluate caprine arthritis encephalitis virus (CAEV) transmission among sheep using 15 lambs that were distributed in 2 experimental groups. The exposed group consisted of 10 lambs that remained with their mothers, who were experimentally infected with CAEV. The non-exposed group was characterized as the control group and was comprised of 5 lambs that remained with their CAEV-negative mothers. Blood samples were collected monthly from birth until 1 year of life. To evaluate the transmission, an agar gel immunodiffusion test (AGID), enzyme immunoassay (ELISA), immunoblotting (IB), and nested polymerase chain reaction (nPCR) techniques were used. The non-exposed group was negative in all of the tests throughout the whole experiment. In the exposed group, 2 individuals had positive nPCR results. Positive nPCR samples were sequenced for comparison with the original goat strains and were shown to be similar to the CAEV-Cork strain. Seroconversion was not detected, and clinical manifestations were not observed. Thus, after 1 year of observation, it was verified that CAEV transmission among sheep is possible; however, with discreet frequency. This was an initial study, and other experiments are needed to analyze the adaptive capacity of the CAEV to remain in an infected sheep flock and cause the disease.